Teachers’ code mixing and code switching: Insights on language barriers in EFL classroom - Nenny Vitriya; Dian Luthfiyati; Tiara Widyaiswara (Jurnal Penelitian Humaniora, 2022)
This research was conducted on Tenth Grade students at a vocational high school in Lamongan, this study aims to describe, explain the form of code mixing and code switching that occurs in learning, find out the factors and reasons teachers use code mixing and code switching in learning English in Tenth Grade . The method used in this study is descriptive qualitative using a sociolinguistic approach. Data collection techniques research results in the form of data collection obtained by means of observation and open interviews at the time of the study. The results showed that code-switching and code-mixing in learning English in one of the vocational high schools in Lamongan City found a form of code mixing and code switching that occurred in learning in Tenth Grade , in total only two types of code mixing were found. The factors causing code-switching include: the speech of the interlocutor, the third presence, the subject (topic), to evoke a sense of humor. Factors causing code mixing include: wanting to explain something, because of the situation, wanting to establish intimacy between teachers and students. The impacts of code switching and code mixing include: positive impacts, namely students are easier to understand the subject matter presented by the teacher, negative impacts of the Indonesian language order resulting from interference and integration, as well as code switching and code mixing. the use of Indonesian is not done properly and correctly so that in learning the situation becomes informal. This research is expected to provide knowledge and become a reference for further research with different references.Key Words: Sociolinguistic, Code Mixing, Code Switching